Analysis of Tenses and Aspects in the Short Story Wajhul Haqiqah by Taufiq Al-Hakim: A Morphosyntactic Study - Vania Acintya Alifah; Irfan Addriadi; Siti Muslikah (Hasanuddin University, 2025)
This study analyzes the system of tense and aspect in verbs within the Arabic short story Wajhul Haqiqah by Taufiq Al-Hakim. The aim is to demonstrate that Arabic verbs not only function as actions but also serve as markers of temporality and aspectuality through their diverse patterns. These varying patterns convey different meanings of time and aspect. Employing a descriptive qualitative method, the research examines the object as it is and presents it in the form of an explanation in the report. Data collection techniques include listening and note-taking. The findings indicate that the short story predominantly utilizes verbs in the past tense with a perfective aspect, indicating actions completed in the past. Additionally, there are present tense verbs that show imperfective aspects, especially when preceded by past tense verbs within the same sentence structure. The study confirms that in Arabic, temporality and aspectuality are determined not only by the form of the verb but also by the particles that accompany it. This research contributes to a deeper understanding of the tense and aspect system in Arabic literature.